Stabilization of As-contaminated dredged sediment using Al- and Fe-impregnated food waste biochar - Hong, Seung Hee; Hwang, Soonho; Lee, Chang Gu; Park, Seong Jik (Journal of Soils and Sediments, 2023)
Purpose: Aluminum- and iron-impregnated food waste biochar (Al-FWBC and Fe-FWBC) have been suggested for the remediation of dredged sediments contaminated with arsenic (As). Materials and methods: Sediment was obtained from a reservoir surrounded by several abandoned gold mines. High As concentration (102.7 mg kg−1) of the sediment corresponded to a severely contaminated level, but other heavy metals were in acceptable ranges without toxic concerns. Al-FWBC and Fe-FWBC, successfully synthesized in a previous study to remove As from aqueous solutions, were used as stabilization/solidification (S/S) agents in the current study. A sequential extraction procedure was applied to investigate the fractionation and stability of As in sediments. Results and discussion: Amendment of Al-FWBC and Fe-FWBC for 6 months reduced the non-specifically and specifically sorbed fractions but increased the residual fraction. Fe-FWBC 1% was most efficient in stabilizing As in the sediment and it decreased 45.4% of non-specifically and specifically sorbed fractions. The effect of Al-FWBC and Fe-FWBC amendments was further confirmed by measuring potential ecological risk, and the contamination factor decreased from a considerably polluted to moderately polluted level. Arsenic and other heavy metals that leached from the S/S-treated sediments via toxicity characteristic leaching procedure did not exceed the values prescribed by the US Environmental Protection Agency. Conclusions: Stabilization/solidification treatment using Al-FWBC and Fe-FWBC, converted from waste to value-added substances for environmental pollution control, can be applied to remediate sediments contaminated with As.
Keywords: Dredged sediment; Food waste biochar; Solidification; Stabilization; TCLP